EVALUASI PENGARUH GEOMETRI SUDUT MATA PISAU MESIN PENCACAH TERHADAP KUALITAS DAN DISTRIBUSI UKURAN HASIL PENCACAHAN - Jeyno Raymon Kandolo; Sigiet Haryo Pranoto; Anis Siti Nurrohkayati; Ananda Sylvano (Badan Penerbit Universitas Muria Kudus, 2026)
This study aims to analyze the effect of blade edge angle geometry on the particle size distribution and quality of shredded materials, ranging from plastic to cardboard, using a rotary cutter–type shredding machine. The blade edge angles investigated in this study were 35° and 60°, with test materials consisting of polyethylene terephthalate (PET) plastic, plastic bags, and cardboard. Operating parameters of the machine, including rotational speed, number of blades, and blade thickness, were kept constant throughout the experiments. The analysis focused on shredding capacity, particle size distribution, and the quality of shredded products in terms of shape uniformity and process stability. The results indicate that the 35° blade angle produces higher shredding capacity, smaller and more uniform particle sizes, and better overall shredding quality compared to the 60° blade angle. In contrast, the 60° blade angle tends to produce longer and less uniform particles, particularly for flexible plastic materials, and increases the likelihood of material clogging during the shredding process. Based on these findings, it can be concluded that a blade edge angle of 35° is the optimal configuration for achieving efficient shredding performance and high-quality plastic output, thereby supporting recycling processes.